A hybrid control system for investigating a high level of decision in internet of things - Mohanad Ali Meteab Al-Obaidi; Basim Jamil Ali; Tole Sutikno; Jamila H. Saud (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In the modern world, the search started for cheap and efficient operating system sources has begun can converted to civilian ends. Internet of things (IoT) is one of the most realistic applications for remote control and remote management using a wide network. In this paper, a control system is designed and built to manage and control traffic lights and street lighting systems, as well as turning on/off generators in a small virtual environment. This was implemented by designing and building a hybrid electronic circuit that combines the closed-circuit control system and the open circuit system. The closed circuit regulates the system according to the desired condition without operator interaction; while the open circuit operates on demand. This type of a hybrid control system demonstrated its high flexibility by controlling devices and its high efficiency compared to the closed circuit and the open circuit system independently. It also helps reduce the number of maintenance guys and energy consumption as well as the cost